Her 2 /Neu Overexpression in Gastric Cancer and its Correlation with Histopathological Grade and Subtype (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: gastric adenocarcinoma; grade a n d subtype; her2/neu overexpression; immunohistochemistry; her 2 scoring in gastric cancer; trastuzumab